Conciliation procedures in civil proceedings of the Republic of Kazakhstan - Shaimenova , A.B. (Bulletin of the Karaganda University “Law Series”, 2019)
In the article the effectiveness of conciliation procedures used in civil proceedings in the Republic of Kazakhstan is analyzed and the features of such pilot project implementation as «Conciliation procedures in court» approved by the Supreme Court of the Republic of Kazakhstan are discussed. The aim of the study is a comprehensive analysis of conciliation practice in resolving civil disputes. The article includes general scientific and special research methods: analysis, synthesis, abstraction, induction, deduction, logical and comparative and legal method. The author conducted a comparative analysis of «Conciliation procedures in court» pilot project in Karaganda region for the period from 2018 to 2019 and presented statistical data on three types of conciliation procedures according to information from the district court № 2 of Kazybek-bi district of Karaganda as well. The author came to a conclusion that conciliation procedures are mainly considered as a part of alternative dispute resolution system (ADR) and are identified with non-jurisdictional conflict resolution methods, which means searching for ways out of the conflict by the parties themselves or dispute resolution between the parties by a third party, which is chosen by mutual agreement of the parties. We believe that arbi tration (arbitration panel) cannot be related to conciliation procedures, as they are jurisdictional ways of resolving disputes, i.e. it is the resolution of various issues arising in law sphere by making a binding (imperious) decision for them by competent authorities.